Training on Cultivation of Fruit Plants in Pots (Tabulampot) for KWT Sida Makmur Pucang Banjarnegara: Pelatihan Budidaya Tanaman Buah Dalam Pot (Tabulampot) Kepada KWT Sida Makmur Pucang Banjarnegara - Wibowo, Sapto Wibowo (Universitas Lancang Kuning, 2024)
Cultivation of fruit plants in pots (tabulampot) has been popular for a long time, especially in urban communities, both as a hobby and as an agricultural business. In terms of aesthetics, tabulampot is interesting to look at and adds to the beautiful yard of the house. The fruit can be enjoyed as family nutrition. So far, the home yard of Pucang Village residents has only been used with vegetable plants planted in polybags. Even if there are residents who plant fruit trees, they are not in pots but planted directly on the yard that has not been cemented. Thus, tabulampot cultivation training is the right solution for the residents of Pucang Village, Banjarnegara Regency. The purpose of this community service activity is to increase the knowledge and skills of Sida Makmur KWT members in Pucang Village intabulampot cultivation. The method used is counseling and demonstration. Counseling contains theoretical material about tabulampot. Demonstrations include making planting media, transplanting plants in pots, and plant care. The results of the training showed that KWT Sida Makmur members took counseling and practice seriously and enthusiastically so that they were able to absorb the tabulampot cultivation training material, and their knowledge and skills increased